Does an intervention designed to improve self‐management, social support and awareness of palliative‐care address needs of persons with heart failure, family caregivers and clinicians?. Issue 3 (13th December 2017) - Sebern, Margaret D.; Sulemanjee, Nasir; Sebern, Mark J.; Garnier‐Villarreal, Mauricio; Whitlatch, Carol J.
Abstract : Aims and Objectives: To conduct a formative evaluation of the iPad‐Enhanced Shared Care Intervention for Partners (iSCIP) among persons with heart failure (HF), family caregivers and clinicians. Together, persons with HF and family caregivers are referred to as partners. Background: There is growing awareness of the caregiver's contributions to HF self‐management, social support and reciprocal benefits of interventions that involve both partners. The iSCIP engages both partners in a six‐session psychosocial intervention to address three preventable causes of poor outcomes in a HF population: poor self‐management skills, inadequate social support and underutilisation of palliative care. An iPad app is used to organise the intervention. The goals of the iSCIP are to engage partners in HF self‐management, communication about the HF patient's care values and preferences, and future planning. Design: A qualitative focus group design was used. Methods: Seven clinicians and eight partners participated in focus groups to explore their experiences, needs and reaction to the iSCIP content and technologies employed. Open‐ended questions and closed‐ended surveys were used to collect data. Deductive content analysis was used to analyse the qualitative data. NVivo software was used for qualitative data analysis. Bayesian statistical models were used to analyse numeric data. Results: The iSCIP met partners' and clinicians' needs to improve self‐management, communicate about care values and preferences and plan for the future. Quantitative analysis of numeric data supported our qualitative findings, in that both groups rated the intervention components useful to very useful. Implications for practice: These findings add to the growing evidence of the feasibility and acceptability of programs that address care values and preferences, and care planning. The iSCIP can be used as a guide for developing interventions and software applications, which involve both partners in care and palliative‐care discussions.